Health Risk Practices Associated with Reoccurrence of Lassa Fever Outbreak among Households in Ebonyi State - Elom, Nwamaka A.; Nnebuife, Deborah; Okere, G.N; Ogba, Okpata Onyekachi; Okeh, Ugochi; Offormah, Chidimma Peace; Asuzu, Nicholas Chukwuemeka; Ngozika, Rita Ojide; Ngwakwe, Patricia C. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2024)
This study determined health risk practices associated with reoccurrence of lassa fever outbreaks among households in Ebonyi State. The study was guided by three research questions and two hypotheses. This study adopted cross-sectional survey research design. The population of the study comprised 5041 head of households in Ebonyi State and 468 participated in the study. A multi stage sampling procedure was used to drawn the participants. The instrument for data collection was structured questionnaire titled: Health Risk Practices Associated with Lassa Fever Questionnaire (HRPALFQ). Overall reliability coefficient of the instrument was r=0.85. Data were analyzed using mean and standard deviation to answer research questions while Analysis of Variance (ANOVA) and t-test statistics were used to test the hypotheses at 0.05 level of significance. Results showed that households in Ebonyi State practice to high extent risk associated with reoccurrence of lassa fever in Ebonyi State (2.96 ±0.39). When ANOVA and t-test statistics were computed, significant differences in the health risk practices associated with reoccurrence of Lassa fever among household in Ebonyi State were observed based on age (f-val 4.557, p=0.004 ) and location (t-value 7.244, p=0.000). The study concluded that households in Ebonyi State practice to high extent health risk associated with reoccurrence of lassa fever. The study therefore, recommended among others that there is need for proper education of households in Ebonyi State through seminar, workshops and conferences on lassa fever by health educators and community health workers.